Assessment of steroid use as a key performance indicator in inflammatory bowel disease—analysis of data from 2385 UK patients. Issue 9 (8th October 2019) - Selinger, Christian P.; Parkes, Gareth C.; Bassi, Ash; Limdi, Jimmy K.; Ludlow, Helen; Patel, Pritash; Smith, Melissa; Saluke, Santosh; Ndlovu, Zandile; George, Becky; Saunders, John; Adamson, Mark; et al.
Summary: Background: Patients with IBD are at risk of excess corticosteroids. Aims: To assess steroid excess in a large IBD cohort and test associations with quality improvement and prescribing. Methods: Steroid exposure was recorded for outpatients attending 19 centres and associated factors analysed. Measures taken to avoid excess were assessed. Results: Of 2385 patients, 28% received steroids in the preceding 12 months. 14.8% had steroid excess or dependency. Steroid use was significantly lower at 'intervention centres' which participated in a quality improvement programme (exposure: 23.8% vs 31.0%, P < .001; excess 11.5% vs 17.1%, P < .001). At intervention centres, steroid use fell from 2015 to 2017 (steroid exposure 30.0%‐23.8%, P = .003; steroid excess 13.8%‐11.5%, P = .17). Steroid excess was judged avoidable in 50.7%. Factors independently associated with reduced steroid excess in Crohn's disease included maintenance with anti‐TNF agents (OR 0.61 [95% CI 0.24‐0.95]), treatment in a centre with a multi‐disciplinary team (OR 0.54 [95% CI 0.20‐0.86]) and treatment at an intervention centre (OR 0.72 [95% CI 0.46‐0.97]). Treatment with 5‐ASA in CD was associated with higher rates of steroid excess (OR 1.72 [95% CI 1.24‐2.09]). In ulcerative colitis (UC), thiopurine monotherapy was associated with steroid excess (OR 1.97 [95% CI 1.19‐3.01]) and treatment at an intervention centre with less steroid excess (OR 0.72 [95% CI 0.45‐0.95]). Conclusions: This study validates steroid assessment as a meaningful quality measure and provides a benchmark for this performance indicator in a large cohort. A programme of quality improvement was associated with lower steroid use.